A Test Case Generation Approach Based on Sequence Diagram and Automata Models. Issue 2 (1st March 2016) - Zhang, Chen; Duan, Zhenhua; Yu, Bin; Tian, Cong; Ding, Ming
Abstract : To improve the test automation in software development process, following the researches on test cases generation technology from models, an incremental test case generation approach is proposed based on finite automata, and Event deterministic finite automata (ETDFA) are employed to describe the sequence diagram models of system interaction. By model checked with Propositional projection temporal logic (PPTL), the correctness of ETDFA is verified. Then we can get the composed automata by synthesis rules, and generate the test cases incrementally by test cases generation algorithm. Case studies are presented to show that this approach enables to improve test cases correctness, and reduce the complexity of test cases generation process.